Impact of postpartum influenza vaccination of mothers and household contacts in preventing febrile episodes, influenza-like illness, healthcare seeking, and administration of antibiotics in young infants during the 2012-2013 influenza season. - Maltezou, Helena C; Fotiou, Aikaterini; Antonakopoulos, Nikolaos; Kallogriopoulou, Cleopatra; Katerelos, Panos; Dimopoulou, Antonia; Tsoutsa, Vasiliki; Tania Siahanidou; Papagaroufalis, Constantinos; Kostis, Evangelos; Papantoniou, Nikolaos; Antsaklis, Aristides; et al. (Clin Infect Dis, 2013)
BACKGROUND: Influenza is associated with an increased risk for serious illness, hospitalization, and mortality in infants aged <6 months. However, influenza vaccines are not licensed for administration in this age group. The study evaluated the effectiveness of postpartum influenza vaccination of mothers and household members in infants. METHODS: The influenza vaccine was offered to mothers and household members of neonates born or hospitalized in 3 hospitals prior to the 2012-2013 season. Mothers were contacted every 2 weeks during the influenza season, and data regarding the onset of fever and/or respiratory symptoms in infants, healthcare seeking, hospitalization, and administration of antibiotics were collected. RESULTS: The study group consisted of 553 mothers who delivered 573 neonates. The influenza vaccine was administered to 841 of 1844 (45.6%) household contacts. Vaccination coverage rates ranged between 41.9% for neonates siblings and 49% for mothers. Five hundred thirty infants were analyzed for vaccine effectiveness. For outcomes in the infant, postpartum maternal vaccination had 37.7% effectiveness against acute respiratory illness (ARI), 50.3% against a febrile episode, 53.5% against influenza-like illness (ILI), 41.8% against related healthcare seeking, and 45.4% against administration of antibiotics. Multiple logistic regression analyses showed that maternal influenza vaccination was significantly associated with a decreased probability for febrile episodes, ARIs, and/or ILIs in infants, related healthcare seeking, and/or administration of antibiotics during the influenza season. Vaccination of other household contacts had no impact. CONCLUSIONS: Maternal postpartum vaccination against influenza was associated with a significant reduction of influenza-related morbidity, healthcare seeking, and antibiotic prescription in infants during the influenza season.